MAPPING INDONESIAN WEB SERIES THEMES: INSIGHTS INTO OVER THE TOP CONTENT DIVERSITY - Syahyuni Srimayasandy; Laelatul Pathia (Faculty of Social Sciences and Humanities Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2023)
The ease of internet access in Indonesia is increasing. This encourages content production on the internet to grow as well, including producing original web series broadcast on over-the-top (OTT) services in Indonesia. Encouraging the creation of content diversity in web series requires mapping content produced within a certain period. This research will map the content of the Indonesian web series broadcast on five OTTs in 2020–2022. This research attempts to map the Indonesian web series themes published from 2020 to July 2022. The method used is a qualitative content analysis by reading various theme elements in the web series. These elements can describe the ideas and impressions created by filmmakers. Thematic elements include (1) plot, (2) emotional or mood effects, (3) character, and (4) style or structure. A popular theme is the theme of romance with a variety of school love. The mood is built through conflicts that are close to everyday life. Style the camera arrangement using cinematic and dynamic shots. The sound arrangement makes a lot of use of dialogue to convey messages. Artistic has a trend to take advantage of the beauty of nature and space. To strengthen the three dimensions of the character, make-up, and wardrobe are used according to the character's character. The results of this study are as follows: A popular theme is romance with a variety of school love. The mood is built through conflicts that are close to everyday life.